ANALISIS SUPPLY CHAIN IKAN TANGKAP DI PELABUHAN PERIKANAN BUNGUS - Viarani, Suci Oktri; Nesti, Lisa; Mufti, Wahyu Fitrianda (Politeknik ATI Padang, 2024)
Padang City is one of the areas with the largest production of caught fish in West Sumatra, reaching 20,191.56 tons or worth IDR 479,442,842,000 in 2021. Fishermen's fish production is influenced by season and weather; if the weather is bad, the number of catches decreases, while during the harvest season, there is an oversupply which causes a lot of fish to be stored in cold storage. Apart from that, the flow of fish caught is not yet clear, causing the use of cold storage to be not optimal. This research aims to ensure that fish catches can be distributed optimally to final consumers, optimize the use of cold storage, and stabilize fish prices on the market to improve the fishermen's economy. The research method used is descriptive and qualitative methods with data collection techniques through field observations and interviews. The research results show that the supply chain for caught fish at the Bungus Fishery Port consists of a supply chain network for large and small catches. This network has three supply chain flows: the flow of goods, information, and money.